DRUG-RESISTANT EPILEPSY: CURRENT CONCEPTS, PATHOGENESIS, RISK FACTORS - Abduvoyitov Bobur Bahodirovich (Research Focus International Scientific Journal, 2025)
Drug-resistant epilepsy (DRE) remains one of the most significant challenges in modern neurology, affecting up to 30–40% of patients despite the availability of more than 20 modern antiepileptic drugs (AEDs). PRE is a multifactorial phenomenon with genetic, molecular, cellular, and acquired mechanisms. Key pathogenetic theories include the target hypothesis, the multidrug transporter hypothesis, and the neural network hypothesis. Acquired mechanisms such as seizure-induced kindling contributes to disease progression and resistance. Risk factors for PRE include early onset of epilepsy, high seizure frequency, febrile seizures, neurological deficits, cognitive impairment, and genetic variability in ion channel and metabolic genes. Structural causes such as cortical malformations, mesial temporal sclerosis, and brain tumors play an essential role in the development of drug resistance. Although surgical treatment achieves seizure freedom in up to 59–80% of patients and significantly improves quality of life, the variability of outcomes and long-term risks remain insufficiently studied. Further research is needed to identify prognostic factors and optimize personalized treatment strategies for PRE.